A program for terpenoid skeleton prediction based on botanical information - Ferreira, M. J P; Alvarenga, S. A V [UNESP]; Macari, P. A T; Rodrigues, G. V.; Emerenciano, V. P. (Elsevier, 2003)
This paper describes a new program developed to the SISTEMAT expert system, the SISOCBOT program. This program employs the botanical data analysis and predicts, at the end of analysis, the probable skeleton of a compound based on the input of family or genus names. The SISOCBOT program was tested with 78 samples involving 302 substances, pertaining to 38 carbon skeletons, and showed a high hit index on skeleton prediction, thus emphasizing the potential importance of these data for structural determination of natural products. © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Botanical information; Expert system; Natural products; Skeleton prediction; Terpenoids; structural analysis